Expanding the agricultural - sanitation circular economy: opportunities and benefits - Banwart, Steven; Carter, Laura; Daniell, Tim; Zhu, Yong-Guan; Guo, Hongyan; Guest, Jeremy; Kirk, Stuart; Evans, Barbara; McKenna, Patrick; Dennis, Sarah (White Rose University Consortium, 2021)
An expanded circular economy between agriculture and sanitation waste (sewage) can recycle essential resources for agriculture through the recovery of water, biomass, and nutrients from sewage at scale. Doing so can help to increase or maintain soil productivity and support agricultural outputs; produce heat and power; reduce Green House Gas (GHG) emissions; and minimise stresses on water reserves.
Keywords: FOS: Earth and related environmental sciences; FOS: Civil engineering